Active Aging Index and Related Factors Among Aged People in Shiraz in 1397 - majid movahed; maryam majidi (Fasa University of Medical Sciences, 2019)
Background & Objective: Aging is one of the important stage in human life. Nowadays world society regards that matter as an important problem. This study aimed at measuring Active Aging Index in Shiraz and its related and affected factors. Materials & Methods: This survey has been done by quantitative method among a sample of Shirazi elders involving 600 cases. Sampling method was hierarchal cluster sampling. Data were collected by questionnaire and interview. Variables were context information, living arrangement, active ageing, social support, mental health, spiritual health and self-efficacy. Results: Mean of AAI was 51.01± 15.2 (from 100). Social support was the most effective factor on AAI and then education, spiritual health, self-efficacy, mental health, age and income be effected respectively. Consequently, those factors explained over 70% of Active Aging variation.  Conclusion: Elders in Shiraz have median activity number. This number of activity is not acceptable for development. Iran population is increasing rapidly. We have to work on this problem more and more. Attention to social support, education and awareness can be very effective in this situation.